Effective Booking System using Extreme Programming Method - Arisiki Pang Raharja; I Gede Juliana Eka Putra; Ni Made Satvika Iswari (International Journal of Informatics and Computation, 2025)
The rapid advancement of digital technology has driven businesses to offer more efficient services, including in the camera rental industry. Klik Kamera is a growing camera rental business that faced challenges in its manual booking process and has inefficient processes. This study aims to design and implement an online booking system to improve service efficiency, data transparency, and customer satisfaction. The system was developed using the Extreme Programming (XP) methodology, which is adaptive to changes in user requirements. This research builds upon concepts from previous related studies but differs in its development approach. The implementation results indicate that the system successfully addressed key issues in the previous booking process. According to the experimental result, the proposed approach can increase user satisfaction through ease of access, faster response times, and a user-friendly interface. Therefore, the proposed system with XP can be an effective approach in enhancing the quality of rental services.